CORTICOSTEROIDS IN THE TREATMENT OF SEVERE COVID-19 LUNG DISEASE: THE PULMONOLOGY PERSPECTIVE FROM THE FIRST UNITED STATES EPICENTER. (November 2020) - Macauley, Precious; Martin, Alvaro; Epelbaum, Oleg
Highlights: Despite a superficial resemblance, care should be taken not to reflexively conflate COVID-19 lung disease with the more familiar entity of ARDS. There is reason to believe that there are histopathological differences between COVID-19 lung disease and ARDS known to complicate influenza From the pulmonology perspective, this distinction has major treatment implications. The argument for corticosteroid use, which is ineffective in ARDS caused by influenza, in COVID-19 lung disease rests on this separation. Abstract: The SARS-CoV-2 pandemic has introduced the medical community to a lung disease heretofore unknown to most clinicians. In much of the discourse about COVID-19 lung disease, the more familiar clinical entity of ARDS has been used as the guiding paradigm. Reflecting on studies in ARDS, particularly that due to influenza, and on data from the SARS-CoV and MERS epidemics, many authorities, including within the discipline of infectious diseases, were initially passionate in their opposition to the use of corticosteroids for lung involvement in COVID-19. The voice of the pulmonology community—the community of lung experts—has continued to be among the quietest in this conversation. Herein we offer our perspective as academic pulmonologists who encountered COVID-19 in its first United States epicenter of New York City. We encourage a conceptual separation between early COVID-19 lung involvement and ARDS. We draw on history with other immune cell-mediated lung diseases, on insights from the SARS-CoV experience, and on frontline observations in an attempt to allay the skepticism towards corticosteroids in COVID-19 lung disease that is likely to persist even as favorable study results emerge.